Developing English Reading Skills Through Pedogigical Technologies - Qizi, Yuldasheva Nigora Rixsiboy (PT. Antis International Publisher, 2024)
This article provides information on the methodology of developing reading skills in English through new pedagogical technologies. These principles relate to the development of reading activities, which are applied during each activity based on the unique circumstances of the students and the pedagogical implications. The application of the pedagogical part in this order is mainly determined by the principles exposed here.